Variations of Nutrients in Gross Rainfall, Stemflow, and Throughfall Within Revegetated Desert Ecosystems - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (Water, Air, & Soil Pollution, 2016)

Comparison of diurnal dynamics in evaporation rate between bare soil and moss-crusted soil within a revegetated desert ecosystem of northwestern China - Ya-Feng Zhang; Xin-Ping Wang; Yan-Xia Pan; Rui Hu (Journal of Earth System Science, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.